Are the tasks of innovation intermediaries changing? Findings of an empirical study from Dunaújváros / Hungary - Éva Gajzágó (European Regional Science Association (ERSA), 2012)
This paper focuses on the efficiency of innovation intermediary organizations and also reviews the connections of intermediaries with regional and local actors emphasizing the human side of innovation. In the beginning I define the organizations and the innovation process as a special market, specify their tasks and then analyze their regional and local impact through a specific example of the current situation and innovation potential of a Hungarian middle sized industrial city, the city of Dunaújváros.
Keywords: O31; O32; 330; innovation intermediary organizations; regional effect; motivation of innovation process' actors